Efficacy of Bacteriocin Extracted from Lactobacillus acidophilus (LAK) against Bacillus cereus in cow raw milk: Abdul-Hadi A. Abd and Thikra M. Ali - Ali, Thikra M. (The Iraqi Journal of Veterinary Medicine, 2015)
Fifty seven out of ninety bovine milk samples were collected from different areas inside and nearby Baghdad which were positive for Bacillus cereus. The isolates were checked on chromogenic Bacillus cereus agar which was specific for detection of B. cereus colonies. The colony appearance, gram stain, spore stain and oxidase lipase monitol catalase tests were carried out to identify this bacterium. Bacteriocin extracted from Lactobacillus acidophilus was used as a tool to control the growth of undesirable B. cereus growth as spoilage and pathogenic bacteria as well as to keep the food more acceptable and safe to consumer. The results of this study showed that bacteriocin (LAK) had 8 a bactericidal effect against B. cereus in refrigeration and room temperatures at pH 4, 7 and 9, respectively. High potency of bacteriocin (LAK) was confirmed by minimum inhibitory concentration at 30, 60 and 120 minutes. It was found that the zone of inhibition of B. cereus by bacteriocin at 4°C and pH 7 was 26 mm. The present study revealed that bacteriocin was highly effective against locally isolated B. cereus.